Analysing methodological issues in short-term monitoring of rare European beech forests restoration. (2nd January 2019) - Maccherini, Simona; Bacaro, Giovanni; Giovannetti, Giangiacomo; Angiolini, Claudia; Chiarucci, Alessandro
Abstract: Monitoring restoration effectiveness implies that restoration measures should be evaluated using multiscale analysis and modelling approaches. In this way, the scale-dependent nature of ecosystem processes and dynamics can be adequately described. Here, we evaluated how grain size (i.e. the dimension of sampling units) and type of data (abundance vs. presence/absence) impact the analysis of the response to restoration management activities aiming at halting the loss of European beech forests with Abies alba in the central Apennines (Italy). The proposed analysis relies on forests sampled in three Sites of Community Importance (SCIs) located in central Italy. For each treatment (reference, control and impact), randomly located multi-scale plots were selected. Vascular plant occurrences were recorded twice in every plot during summer 2010 or 2011 (before restoration) and in 2013 or 2014 (after restoration). Analysis of species abundances, recorded at the largest grain size available (20 X 20 m plot), showed a significant change in plant species composition in restored sites just after two years from the restoration management. When presence/absence data were used previous results were less visible, for all the examined grains, in two out of the three sites, suggesting a site-dependent response.